Upaya Berteologi Kontekstual Dalam Ketidaksetaraan Perempuan dan Laki-Laki di Keluarga - Fitri Lyli Septiani Sitompul; Debora Retinawati Nababan; Berlina Simatupang; Andika Sinaga; Belaster Purba; Destana S R Banurea (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Family is a fundamental component in individual and societal life that builds emotional bonds between its members such as father, mother and children. The family provides a safe and harmonious environment where the roles of parents and children complement each other. However, gender inequality often occurs in families, especially towards women, due to patriarchal culture. Patriarchy is a social system that considers men as the main authority which influences the views and treatment of women in various aspects, including education and the distribution of domestic roles. Women are often thought to not need higher education or work, being assigned more to housework, while men are prioritized in education and decision making. To overcome gender inequality in the family, contextual theological efforts are needed by applying religious and moral values ​​that teach equality, justice and compassion. With religious teachings that emphasize mutual love and respect, families can create a more just and harmonious environment, where roles and responsibilities are divided based on ability, not gender. This approach aims to support equality and justice in the family, so that religious teachings can become an inspiration for positive social change, including overcoming gender inequality.